Enemy parole. (July 2023) - Dagan, Netanel
Pushing and expanding the boundaries of the 'criminology of the other' and 'enemy penology' to the post-sentencing phase, this study aims to analyse parole for terror-related prisoners. For doing so, the study thematically analysed 207 decisions of the Israeli parole board for individuals labelled as 'security prisoners'. It found that for security prisoners, the parole board employs a distorted version of the more discretionary-individualised logic that applies to ordinary prisoners. When performing such 'enemy parole' – and overwhelmingly denying parole to security prisoners – the parole board uses three conflicting discourses: security-group logic, responsibilisation and resentencing . Through these discourses, the parole board negotiates the categories of self/other and citizen/enemy in order to suspend the reintegrative components of 'citizen parole'. In conclusion, 'enemy parole' is constructed as an exclusionary, punitive and exceptional process disguised as inclusionary, equal and legitimate.